1989
DOI: 10.1007/bf00339737
|View full text |Cite
|
Sign up to set email alerts
|

Sequences responsible for the tissue specific promoter activity of a pea legumin gene in tobacco

Abstract: Maturing pea cotyledons accumulate large quantities of storage proteins at a specific time in seed development. To examine the sequences responsible for this regulated expression, a series of deletion mutants of the legA major seed storage protein gene were made and transferred to tobacco using the Bin19 disarmed Agrobacterium vector system. A promoter sequence of 97 bp including the CAAT and TATA boxes was insufficient for expression. Expression was first detected in a construct with 549 bp of upstream flanki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(96 citation statements)
references
References 26 publications
2
94
0
Order By: Relevance
“…1B). Several root tissue-specific cis-acting sequences (ATATT) were localized, as well as three CAAT box-like sequences at positions 27, 243, and 2323 that have been found in promoters of genes encoding seed storage protein (Shirsat et al, 1989). The ATTTTTA sequence is related Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…1B). Several root tissue-specific cis-acting sequences (ATATT) were localized, as well as three CAAT box-like sequences at positions 27, 243, and 2323 that have been found in promoters of genes encoding seed storage protein (Shirsat et al, 1989). The ATTTTTA sequence is related Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the ciselements analysis confirmed that the functional diversities of the MtDof genes are mainly involved in tissue development, response to environmental stress, and interactions with other TFs. For example, motifs related to tissue development, including CAATBOX1 related to tissue-specific promoter activity (Shirsat et al, 1989), ROOTMOTIFTAPOX1 related to root development (Elmayan and Tepfer, 1995), POLLEN1LELAT52 and GTGANTG10 related to flower development (Rogers et al, 2001;Filichkin et al, 2004), and CACTFTPPCA1 related to leaf development (Gowik et al, 2004), were extensively present in the MtDof genes, and thus, most of these were highly expressed in roots, blades, buds, flowers, and seedpods. In addition, light responsive elements were also identified, such as GT1CONSENSUS (Terzaghi and Cashmore, 1995), and these were widely represented in the MtDof genes.…”
Section: Discussionmentioning
confidence: 99%
“…affrc.go.jp/htdocs/PLACE/; Higo et al, 1999) indicated that the putative promoter contained four copies of the pollen-specific motifs (AGAAA) (POLLEN1LELAT52, Bate and Twell, 1998) and some other motifs associated with seed storage protein genes (CAATBOX1, Shirsat et al, 1989; EBOXBN-NAPA, Stalberg et al, 1996;and CANBNNAPA, Ellerstrom et al, 1996). To characterize tissue specificity of LeMAN5 expression, the 5Ј-upstream region of this gene (Ϫ543 to ϩ38) was cloned into a promoterless vector encoding a GUS gene to create a reporter vector.…”
Section: Characterization Of Leman5 Promoter In Arabidopsismentioning
confidence: 99%